Is an internal comparison better than using national data when estimating mortality in longitudinal studies?. Issue 9 (11th August 2006) - Card, T R; Solaymani-Dodaran, M; Hubbard, R; Logan, R F A; West, J
Abstract : Background: Discrepancies between the results of different studies looking at mortality in similar disease cohorts led us to consider the impact of methodology upon outcome. Methods: Cohort studies were carried out using age, sex, practice, and calendar time matched control groups in the general practice research database. Data were used on all subjects with inflammatory bowel disease, coeliac disease, or Barrett's oesophagus. Mortality data for the population of England and Wales were obtained from the UK Office for National Statistics. The study compared hazard ratios (HR) for mortality using the matched controls to those found when an indirect standardisation to the mortality experience of England and Wales was carried out. Results: For all three conditions the mortality risk was slightly lower when the national population data were used compared with the internal comparison group (coeliac disease HR 1.33 v standardised mortality ratios (SMR) 1.25, Barrett's oesophagus HR 1.32 v SMR 1.32, inflammatory bowel disease HR 1.50 v SMR 1.34). Conclusions: A bias was found towards underestimating mortality risk when cohort studies use national population death rates as a comparator. Estimates obtained when an internal comparison group has been used are probably more appropriate.